Bibliometric Analysis of Hydrogel Research Using VOSviewer Indezed by Google Scholar - Annifah, Riri Uswatun; Nandiyanto, Asep Bayu Dani (Applied Research in Science and Technology, 2025)
This study used bibliometric analysis using VOSviewer indexed by Google Scholar to evaluate research trends in hydrogels. The analysis covered publications from 2018 to 2022. The study found an increasing number of publications related to hydrogel research over the five years, indicating increasing interest in this area. Using VOSviewer, this study identified research topics related to hydrogels. Data obtained and collected using Publish or Perish software. The data obtained is based on the keywords "hydrogel, wound dressing, production". Based on the analysis carried out, 750 articles were obtained that were relevant to the keywords used in the 2018-2022 period. The results showed that hydrogel production increased from 2018-2022. This research is expected to help and become a reference for other studies as material for consideration in determining the research theme to be taken.